Nursing Care for Pregnant Women with COVID-19: A Characterization Based on Narrative Review - Monroy Herrera, Ludy Esther; Manrique Peña, Stefany; Pulido Montes, Maria Andreina; Rincón Romero, Katherine (Salud Integral y Comunitaria, 2026)
Introduction: the COVID-19 pandemic represented a global health emergency with particular implications for pregnant women, who were considered a vulnerable population due to associated clinical and psychosocial risks. In this context, nursing professionals played a key role in direct care, facing challenges related to the novelty of the virus, resource limitations, and the need to adapt protocols in real time. Objective: to characterize nursing care for pregnant women with COVID-19. Methods: A narrative literature review was conducted in April 2023. Scientific articles and technical documents published in English, Spanish, or Portuguese over the past five years were included, focusing on nursing interventions in pregnant women diagnosed with COVID-19 in outpatient or primary care settings. The search was carried out in databases such as PubMed, ScienceDirect, ResearchGate, Dialnet, and SciELO, using descriptors in three languages. From a total of 1030 records, 16 studies were selected for qualitative synthesis. Results: identified interventions included clinical actions such as oxygen saturation monitoring, postural changes, and non-pharmacological therapies, as well as psychosocial support, effective communication, and health education. Institutional barriers, social inequalities, and psychological impacts on both pregnant women and healthcare personnel were documented. Strategies varied by geographic context, highlighting hybrid care models and the need for humanized approaches. Conclusions: nursing care for pregnant women with COVID-19 was characterized by an integrative approach combining clinical and psychosocial actions, within a complex environment marked by structural limitations and continuous adaptation.